Internet and hiv/aids: a virtual ethnography on Facebook - Alfredo de Oliveira Neto; Kenneth Rochel de Camargo Júnior
This paper identified and analyzed some interactions on the internet in the daily of people living with HIV and AIDS (PLHA) in Brazil. As methods we made interviews with PLHA analyzed by content analysis and a virtual ethnography of a secret group of PLHA on Facebook. These are the following results: sociability produced in the internet helps to reduce suffering in relation to prejudice; there are not many welcoming zones for PLHA on the internet; PLHA linked to social networks have more encouragement to not give up the medication; negotiations about medication and symptoms take place in social networks. We conclude that there is a need to have welcoming zones to PLHA on the internet guaranteed by public policy; medical education needs to cover issues related to the internet and health.